AUTOMATED HAND WHEELCHAIR FOR DISABLED PEOPLE USING MEMS TECHNOLOGY - M.Krishna; A. Vinitha; Shivprasad, Lingampally; Shivprasad, D. Priyanka (International Journal of Psychosocial Rehabilitation, 2019)
The interaction between man and machines has become an important topic for the robotic community as it can generalize the use of robots. With the advancement of technology, different devices are being developed in almost each and every field. With these new devices different applications are also being developed and here is one of such latest inventions “Hand Gesture based Robot”. Like we know to control any robot, generally we give some command inputs by pressing some keys, etc to control its direction. But here in this project work, we need not to press any keys, instead by moving the hand in one direction automatically the robot will also move in that particular direction. So depending on the movement of the hand, the robot direction is controlled. This is possible using the MEMS technology. MEMS stand for Micro Electro Mechanical System. As the robot is wireless control, the MEMS is interfaced to the micro controller in the remote and the wireless information is transmitted through the RF transmitter. The control module will be the MEMS interfaced with the controller to generate command codes and the same is transmitted. Depending on these command codes the micro controller present on the robot, gives instructions to the motors to move in specific directions. The MEMS is like a motion sensor. Slight variation in the X, Y, or Z – axes gives us the voltage variation that is fed to the ADC and the digital information is fed to the controller in the remote. This information is encoded and is transmitted through the RF transmitter. The RF receiver on the robot receives this encoded information and will be given to the controller which decodes the data and operates the robot.